Analysis of Inflation and Poverty Levels on the Climate of Economic Growth in Jambi Province - Ary Dean Amry; Kasmiyati; Dwi Narti (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
Inflation is the tendency of prices to rise generally and continuously. Based on data from BPS, the amount of inflation in Jambi City in 2022 is 0.79 %. CPI (Consumer Price Index) In Jambi City was 114.90. It shows that the growth of the Islamic economy is relatively low. The purpose of this study is to find out and analyze how the effect of inflation on the climate of Islamic economic growth in Jambi Province. This quantitative research was conducted in time series from 2011 to 2022. From the data obtained, the poverty rate influences 59% of the climate index of Islamic economic growth in Jambi Province. Showing that inflation does not affect Islamic economic growth because when the climate rate of Islamic economic growth increases by 1%, the inflation rate decreases by 1.55, which certainly has a very positive impact on the Islamic economic growth climate. Efforts are needed to increase the value of the Climate Index of Islamic economic growth, hoping that human progress will continue to develop. Â